Raspberry Pi retail applications : transform your business with a low-cost single-board computer - Wu, Elaine; Maslov, Dmitry (Apress, 2022)
Increase productivity and lower the operating cost of your business by automating crucial business processes with the Raspberry Pi. After completing this book's projects you'll be able to determine the best way to quickly apply automation to existing systems and processes in your retail outlet with Raspberry Pi. Youll start by composing ideas to transform your business, and then gain practical, accessible methods for executing them. Find real-world ways to implement tech solutions to accelerate the growth of your business, and navigate the ever-changing landscape of retail automation with this book. Then see what automation can and cannot do at the current level of technical progress for retail businesses. By comparing the efficiency of machines with manual labor, youll be able to assess how open-source hardware performs in lowering operating costs and identify business components that can be improved with automation. Raspberry Pi Retail Applications features projects that are easy to dive into and will function readily in your day-to-day business right now. You will: Identify business components that can be improved with automation Combine the existing array of Raspberry Pi hardware options to build customized solutions Implement tech ideas in a practical retail environment to reduce cost and streamline your business processes .